Influence of Febrile Seizure in Children’s Neurodevelopment - Kanta, Shayla Imam; Khan, Naila Zaman; Mahmud, KM Sarwar (Dhaka Shishu (Children) Hospital Journal, 2022)
Background: Febrile seizure is one of the most common diseases in early childhood. The impact of early-life Febrile Seizure on the developing brain is an important issue to detect. Objectives: To observe the neurodevelopment of children suffering from different types of febrile seizures. Methods: This was a prospective observational study; the study was conducted in Dhaka Shishu (Children) Hospital, Dhaka from July 2012 to August 2013. Total 71 children were included in the study who fulfilled the selection criteria. History was taken thoroughly. Rapid neurodevelopmental assessment (RNDA) was performed for initial assessment and subsequent follow up and was advised accordingly. Results: Total 71 cases were included where mean age was 17.76±8.03 months, median was 16 months; in both the group male child had slight high preponderance. Majority of seizures were <10 minutes duration in both group which was not statistically significant. Important postictal event was found, 12 cases (26.7%) in simple seizure and 16 cases (61.5%) in complex seizures which was found statistically significant, but there was no risk for further seizure. On follow up, RNDA detected risk of impairment in vision, cognition, speech and behavior. In complex group statistically significant association was found with impairment of cognition only at initial and follow up at 3 month. Conclusion: Neurodevelopment impairment is not influenced by types of febrile seizure but significant cognitive impairment was found in complex seizure. DS (Child) H J 2021; 37(1): 45-50